Implementation of Value-Based Islamic Pesantren Curriculum Management in Improving the Quality of Santri Education in the Modern Era - Dewi Ratnawati; Ngatiyah; Subekti; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
This study is motivated by the importance of adaptive curriculum management in Islamic boarding schools, considering that many curricula remain traditional and less integrated with modern demands. The purpose of this research is to analyze the implementation of curriculum management in improving the quality of students’ education. This study employs a qualitative approach using a literature review method, drawing from books, academic journals, and relevant references on Islamic education management. The findings reveal that effective curriculum management in pesantren must involve four main functions: planning, organizing, implementing, and evaluating in an integrated manner. Furthermore, the integration of traditional curriculum based on classical Islamic texts with modern competency-based curriculum has proven to enhance students’ intellectual, spiritual, and social quality. Additional findings indicate that supporting factors such as teacher quality and the use of technology significantly influence curriculum success, while major obstacles include limited facilities and resistance to change. Therefore, innovative curriculum management is essential to improve the competitiveness of pesantren in the modern era